Multisteps Global Kinetic Analysis of MSW Slow Pyrolysis - Himawanto, Dwi Aries (IPTEK The Journal for Technology and Science, 2025)
The goal of this research is to find relationships between single components slow pyrolysis characteristics and mixed component slow pyrolysis characteristics of segregated municipal solid wastes (MSW). The material of this research consists of organic wastes (bamboo wastes and banana leaves wastes) and inorganic wastes (styrofoam wastes and snack wrapping wastes. The materials which used to study were the unprosessing waste. The samples were collected, dried and crushed until passing 20 mesh shieves then characterized in self manufactured macro balance. The thermogravimetry analyses were done to find the MSW slow pyrolysis characteristics. The 20 gram sample was placed in the furnace whose temperature is increased with 10 0C/min heating rate until reached 400 0 final temperature and held for 30 minutes before the sample is cooled into room temperature. One hundred ml/min nitrogen introduced from the bottom of furnace as a swept gas. The results of the research show that the global kinetic method could be used to predict the MSW single component activation energy but it should be modified to calculate the mixed sample activation energy . The predictive activation energy values which calculated based on weighed sum of single component have 18.5 % deviations if compared with experimental result.